Morocco to convert 1M Ha to conservation Agriculture - How ICARDA/INRA Fit in - Moussadek, Rachid; Nangia, Vinay; Devkota Wasti, Mina Kumari (ICARDA Communication Team, 2023)
Conservation Agriculture is a sustainable agricultural production system guided by three core principles: no (or minimal) tillage to the soil after harvest; permanent soil cover to lock in moisture and reduce evaporation; and crop diversification replacing monocropping - to enhance soil health and subsequently improve crop productivity and household resilience.